1999
DOI: 10.1046/j.1365-2125.1999.00095.x
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study on the risk of acute liver injury among users of ketoconazole and other antifungal drugs

Abstract: Ketoconazole and itraconazole were the two oral antifungal associated with a marked increase of clinical acute liver injury. The risk associated with ketoconazole should be taken into account when prescribing it as initial treatment for uncomplicated fungal infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(78 citation statements)
references
References 30 publications
3
74
1
Order By: Relevance
“…In this study, main selection criteria regards the role code assigned to the drug (i.e., only "Primary Suspect", "Secondary Suspect" or "Interacting", whereas cases where antimycotics were reported as "Concomitant" were not included) and information on age and gender (records with missing of mild, asymptomatic, reversible elevations in serum transaminases has been estimated to be 5%-10% [29] . Also García Rodríguez et al [30] found that ketoconazole was associated with significant risk. Very recently, a systematic review and meta-analysis documented an overall incidence of 3.6%-4.2%, which may be considered as common [31] .…”
Section: Data Selection and Analysismentioning
confidence: 99%
“…In this study, main selection criteria regards the role code assigned to the drug (i.e., only "Primary Suspect", "Secondary Suspect" or "Interacting", whereas cases where antimycotics were reported as "Concomitant" were not included) and information on age and gender (records with missing of mild, asymptomatic, reversible elevations in serum transaminases has been estimated to be 5%-10% [29] . Also García Rodríguez et al [30] found that ketoconazole was associated with significant risk. Very recently, a systematic review and meta-analysis documented an overall incidence of 3.6%-4.2%, which may be considered as common [31] .…”
Section: Data Selection and Analysismentioning
confidence: 99%
“…The most common reported adverse events were stomach pain, diarrhea, and rash [50-53]. Itraconazole is reported to cause acute liver injury at an incidence rate of 10.4 per 100,000 [54]. Therefore, it is recommended to obtain baseline ALT and AST before initiating treatment [55].…”
Section: Itraconazolementioning
confidence: 99%
“…Our results suggest that the activation of PXR by clotrimazole is less effective on the transcriptional activation of MRP3 in HepG2 cells. We therefore focused on the hepatotoxicity of azole antifungal agents (García Rodríguez et al, 1999;Kuroda et al, 2004;Girois et al, 2005), because it has been reported that Mrp3 expression is significantly increased in cholestasis-induced liver injury (Wagner et al, 2003). To confirm the cytotoxicity of clotrimazole, LDH activity was measured in HepG2 cells treated with clotrimazole or rifampicin.…”
Section: Novel Transactivation Of the Mrp3 Genementioning
confidence: 99%